Fibroblast growth factor receptor 3 protein is overexpressed in oral and oropharyngeal squamous cell carcinoma. (28th December 2015) - Koole, Koos; van Kempen, Pauline M. W.; Swartz, Justin E.; Peeters, Ton; van Diest, Paul J.; Koole, Ron; van Es, Robert J. J.; Willems, Stefan M.
Abstract: Fibroblast growth factor receptor 3 (FGFR3) is a member of the fibroblast growth factor receptor tyrosine kinase family. It has been identified as a promising therapeutic target in multiple types of cancer. We have investigated FGFR3 protein expression and FGFR3 gene copy‐numbers in a single well‐documented cohort of oral and oropharyngeal squamous cell carcinoma. Tissue microarray sets containing 452 formalin‐fixed paraffin‐embedded tissues were immunohistochemically stained with an anti‐FGFR3 antibody and hybridized with a FGFR3 fluorescence in situ hybridization probe. FGFR3 protein expression was correlated with clinicopathological and survival data, which were retrieved from electronic medical records. FGFR3 mRNA data of 522 head and neck squamous cell carcinoma (HNSCC) were retrieved from The Cancer Genome Atlas (TCGA). Fibroblast growth factor receptor 3 (FGFR3) protein was overexpressed in 48% (89/185) of oral and 59% (124/211) of oropharyngeal squamous cell carcinoma. Overexpression of FGFR3 protein was not related to overall survival or disease‐free survival in oral (HR[hazard ratio]: 0.94; 95% CI: 0.64–1.39; P = 0.77, HR: 0.94; 95% CI: 0.65–1.36; P = 0.75) and oropharyngeal squamous cell carcinoma (HR: 1.21; 95% CI: 0.81–1.80; P = 0.36, HR: 0.42; 95% CI: 0.79–1.77; P = 0.42). FGFR3 mRNA was upregulated in 3% (18/522) of HNSCC from the TCGA. The FGFR3 gene was gained in 0.6% (1/179) of oral squamous cell carcinoma but no amplification was found in oral and oropharyngeal squamous cell carcinoma. In conclusion, FGFR3 protein is frequently overexpressed in oral and oropharyngeal squamous cell carcinoma. Therefore, it may serve as a potential therapeutic target for FGFR3‐directed therapies in oral and oropharyngeal squamous cell carcinoma. Abstract : FGFR3 is frequently aberrated in HPV‐positive head and neck cancers and it has been identified as a candidate therapeutic target. Here, we show that FGFR3 protein is frequently overexpressed in oral and oropharyngeal cancer.